Palladium mediated selective cleavage of benzyl and allyl phosphates: a convenient non-hydrogenolytic method for the synthesis of phosphates and phospholipids. - Mart, Alson; Sarkar, Nitai N.; Shashidhar, Mysore S. (ChemistrySelect, 2022)
Palladium(II) hydroxide on carbon is a catalyst routinely used for the cleavage of O-benzyl groups by hydrogenolysis to obtain the corresponding parent organic compound. The work described in this article shows that allyl and benzyl phosphates, can be cleaved efficiently and selectively using palladium(II) hydroxide on carbon, under non-hydrogenolytic and neutral conditions, precluding the migration of acyl groups. The utility of these cleavage reactions for the synthesis of diacylglycerol and phosphatidic acid, containing unsaturation, is demonstrated. These methods have high potential for the synthesis of a variety of phosphates and natural phospholipids.
Keywords: Carbohydrate; Ether cleavage; Palladium; Phosphate; Phospholipid; Protecting group